2000
DOI: 10.1001/archinte.160.4.541
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Intensive Care for Patients With Human Immunodeficiency Virus Infection

Abstract: Background:Intensive care for patients with human immunodeficiency virus is common, costly, and associated with high morbidity. Accurate and up-to-date outcome and prognostic data are needed to effectively counsel patients and to make difficult decisions regarding admission to the intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
92
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 31 publications
16
92
3
2
Order By: Relevance
“…These factors suggest that patients who died during hospitalization were more likely to present with poor performance status and more advanced and severe disease, leading to death early in their hospital stay. Even though CD4 counts ≤ 200cells/mm 3 were predictive of death in our cohort, some studies have reported contrary findings [23,24].…”
Section: Discussioncontrasting
confidence: 84%
“…These factors suggest that patients who died during hospitalization were more likely to present with poor performance status and more advanced and severe disease, leading to death early in their hospital stay. Even though CD4 counts ≤ 200cells/mm 3 were predictive of death in our cohort, some studies have reported contrary findings [23,24].…”
Section: Discussioncontrasting
confidence: 84%
“…The prognostic factors of mortality in HIV-infected patients admitted to the ICU are acute illness severity, poor functional status, low albumin rate, and respiratory failure requiring mechanical ventilation [47][48][49][50][51][52][53]. However, specific HIV characteristics (CD4 cell count, plasma HIV-RNA load, HIV-related diagnosis, or antiretroviral therapy) have not been clearly identified as predictors of ICU mortality [4,15,37,38,[49][50][51][52][54][55][56][57][58][59], although some reports have associated CD4…”
Section: Discussionmentioning
confidence: 99%
“…Until the mid-90 ties, respiratory failure associated predominantly with Pneumocystis pneumonia (PCP) was the main reason for ICU hospitalization of HIV patients associated with high mortality [5,6]. Further studies, connected with the introduction of HAART, have demonstrated improved survival, even amongst PCP patients [7,8]. At present, respiratory failure is still the most common indication for ICU admission [9,10], although PCP as a cause of respiratory failure is substantially less common.…”
Section: Discussionmentioning
confidence: 99%